ANALYSIS OF FINANCING PRODUCT SERVICES KSPPS AL-ISHLAH MITRA SEJAHTERA PLUMBON DURING COVID-19 DISASTER - Hafni Khairunnisa; Apriyana (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
The rapid spread of COVID-19 has had a major impact on the Indonesian economy. Three biggest impacts occurred, firstly, the decline in people's purchasing power from 5.04% to 2.4%, secondly, prolonged uncertainty made investment weaker, which made the business world sluggish and declined, thirdly, the spread of COVID-19 throughout the world. the world makes the global economic decline which causes commodity prices to also fall. Financing based on sharia principles is the provision of money or an equivalent claim based on an agreement between the bank and another party that requires the party being financed to return the money or claim after a certain period of time with compensation or profit-sharing. The Sharia Savings and Loans Cooperative (KSPPS) is a microfinance institution that collects funds from the public and distributes them to people who need these funds. This type of research is descriptive and qualitative. The result of this study is that KSPPS Al Ishlah Mitra Sejahtera Plumbon is still running financing with various considerations for the welfare of its members.